Assessment of the effectiveness of PAH-specific therapy, including selexipag, in patients with idiopathic pulmonary hypertension according to a comprehensive examination using Raman spectroscopy - E. S. Allakhverdiev; E. A. Rezukhina; O. V. Slatinskaya; O. V. Rodnenkov; Zh. V. Bochkova; N. A. Brazhe; G. V. Maksimov; T. V. Martynyuk (Евразийский Кардиологический Журнал, 2023)
Aim: to assess the effectiveness of PAH-specific therapy, including selexipag, based on data from a comprehensive examination and assessment of oxygen transport function in patients with IPAH using Raman spectroscopy.Materials and methods. The study was performed on fourteen (n=14) patients diagnosed with IPAH who were on combination PAH-specific therapy, including selexipag. The diagnosis was established in accordance with the algorithm proposed in the Russian guidelines for the diagnosis and treatment of PAH (2020). A comparative analysis of clinical and hemodynamic parameters, including an assessment of hemoglobin conformation using Raman spectroscopy, was performed in all participants.Results. The use of Selexipag as part of a combined PAH-specific therapy caused significant changes in the conformation of Hb including a decrease in the probability of a “dome-shaped” heme conformation due to changes in the group vibrations of heme pyrrole groups (I1375/I1172) and stretching vibrations of vinyl groups (I1580/I1550), as well as an increase globin density.Conclusion. The use of the prostacyclin receptor agonist selexipag as part of a combination PAH-specific therapy for patients with IPH was associated with improvement in clinical, functional and molecular parameters (taking into account the assessment of oxygen transport function and hemoglobin conformation by Raman spectroscopy).